(Re)discovering C. S. Song: Mission Studies, Theology and the Future of the Ecumenical Landscape - Aldous, Benjamin (Studies in world christianity, 2025)
When Taiwanese theologian Choan-Seng Song died in late November 2024 there was almost no reaction from UK theologians and scholars, yet ‘Song had a career spanning nearly five decades, a massive theological corpus (that) testifies of his longstanding commitment to theology in Asia’ (Lee 2023: 297). He held important roles at the World Council of Churches (WCC) and was the President of the World Communion of Reformed Churches (WCRC). This article seeks to (re)discover the person and missiological writings of Song as a theologian of ‘extraordinary depth and insight who wove together faith, culture, and a commitment to liberation’. The article is framed by outlining Finnish missiologist Mika Vähäkangas’ recent challenge concerning the future of the academic discipline of mission studies before exploring C. S Song's theology of mission in re-construction and finally asking what this might mean for the ecumenical landscape in England.